Implementation of a Knowledge Management System (KMS) in Small and Medium Enterprises (SME) / Nurul Ainna Hassan - Hassan, Nurul Ainna (Universiti Teknologi MARA Shah Alam, 2020)
Abstract. Most knowledge management (KM) and knowledge systems (KMS) articles have been through in recent years. Although Nonaka has long presented the Theory of Knowledge Management (KM) through his paper since 1994, the research in this field is still intensively discussed. The phenomenon of dynamic research related to this often occurs in parallel with the development of technology, culture, needs and conditions of implementation. The technological development is becoming more and more advanced and also able to solve the problem that always being faced by a human being.